2016
DOI: 10.1038/nature19327
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule stabilization of the KSR inactive state antagonizes oncogenic Ras signalling

Abstract: Deregulation of the Ras–mitogen activated protein kinase (MAPK) pathway is an early event in many different cancers and a key driver of resistance to targeted therapies1. Sustained signalling through this pathway is caused most often by mutations in K-Ras, which biochemically favours the stabilization of active RAF signalling complexes2. Kinase suppressor of Ras (KSR) is a MAPK scaffold3–5 that is subject to allosteric regulation through dimerization with RAF6,7. Direct targeting of KSR could have important th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
99
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(102 citation statements)
references
References 31 publications
3
99
0
Order By: Relevance
“…A small molecule ligand of the JH2 pseudokinase domain of Tyk2, a member of the Janus tyrosine kinase family, was able to lock in a conformation that stabilizes an autoinhibitory interaction with the JH1 catalytic domain, thereby blocking Tyk2-mediated signaling important in autoimmunity [52]. A new class of pseudokinase antagonists was developed that stabilize a previously unrecognized inactive state of the scaffold protein KSR (kinase suppressor of Ras) [53]. In combination with MEK inhibitors, these compounds inhibited growth of Ras mutant cell lines, providing a new therapeutic strategy against Ras-driven cancers.…”
Section: Alternative Approaches To Pki Developmentmentioning
confidence: 99%
“…A small molecule ligand of the JH2 pseudokinase domain of Tyk2, a member of the Janus tyrosine kinase family, was able to lock in a conformation that stabilizes an autoinhibitory interaction with the JH1 catalytic domain, thereby blocking Tyk2-mediated signaling important in autoimmunity [52]. A new class of pseudokinase antagonists was developed that stabilize a previously unrecognized inactive state of the scaffold protein KSR (kinase suppressor of Ras) [53]. In combination with MEK inhibitors, these compounds inhibited growth of Ras mutant cell lines, providing a new therapeutic strategy against Ras-driven cancers.…”
Section: Alternative Approaches To Pki Developmentmentioning
confidence: 99%
“…Indeed, based on the direction of pharma and some of the patent literature, it is certain that scientists are attempting to target pseudoenzymes, both knowingly and (thought provokingly) unknowingly. The likely conservation of structural fold, and a reliance on protein–protein interactions for outputs, mean that pseudoenzymes might be targeted therapeutically in essentially the same ways as other enzymes (see, for example, [2628]). Indeed, in the case of pseudokinases, it was found that promiscuous inhibitors that target the ATP-binding cleft of conventional protein kinases could also bind the equivalent site in pseudokinases despite most of the examined pseudokinases exhibiting no detectable ATP-binding capacity [10].…”
Section: Can Pseudoenzymes Be Therapeutically Targeted?mentioning
confidence: 99%
“…These studies includes the nucleotide exchange blockage [6, 7], Ras association with son of sevenless homologue (SOS) [810], and Ras–Raf interaction [11, 12]. In the past, some approaches were used to target Ras via the KSR due to its pseudokinase standing and non-catalytic function, but now it is a more favorable targeted pathway for designing drugs [13, 14]. The RAS–RAF–KSR–MEK1 pathway proteins work in a cascade.…”
mentioning
confidence: 99%
“…Recently, Dhawan et al [14] published a paper entitled “Small molecule stabilization of the KSR inactive state antagonizes oncogenic Ras signalling” in Nature journal. They targeted the RAS signaling pathway by interfering in KSR, using small molecules as inhibitors that arrest the KSR–MEK1 in an inactive conformational state.…”
mentioning
confidence: 99%
See 1 more Smart Citation